The Role of Audit Quality as a Moderating Variable in Relationship Between Quality of Audit Committee, Company Size and Financial Report Integrity of Manufacturing Companies Listed in IDX - Dede Hertina; Okma Yendri; Yoesoep Edhie Rachmad; Hendrik Elisa Sutejo Samosir; Halim Dwi Putra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
With audit quality serving as a moderating variable, the goal of this study is to examine and collect empirical data on the impact of audit committee quality and business size on the caliber of financial reports. Accounting knowledge, committee size, and meeting frequency all indicate the quality of an audit committee. Manufacturing businesses that were listed on the Indonesia Stock Exchange between 2013 and 2016 were used as a sample in this study. 33 manufacturing enterprises with a 4 year observation period were included in this study. Purposive sampling was used to collect the data. The multiple regression model and moderated regression analysis were used in this study to examine the hypotheses. The findings of this study revealed that the caliber of financial reports was unaffected by the audit committee's experience, the frequency of its meetings, or the size of the accounting and financial firms. Regarding the moderating influence of audit quality, the findings indicated that it was unable to moderate the relationship between the business size and the integrity of financial reports and all audit committee quality proxies.